Tolerability of different oral iron supplements: a systematic review - Cancelo-Hidalgo, María Jesús; Castelo-Branco, Camil; Palacios, Santiago; Haya-Palazuelos, Javier; Ciria-Recasens, Manel; Manasanch, José; Pérez-Edo, Lluís (Current medical research and opinion, 2013)
A systematic review was conducted to analyze the tolerability of several oral iron supplements based on data obtained in available publications and to report the incidence of adverse effects (AEs) for each supplement both overall and gastrointestinal. Electronic databases - Medline, the Cochrane Library, and Embase were searched for studies published up to January 2009. Clinical or observational studies reporting data on the tolerability of oral iron supplements were included. Results were described statistically and a quasi-binomial logistic regression model was developed to evaluate and compare the tolerability of the supplements studied. For this review 111 studies were included, with data on 10,695 patients. Ferrous sulfate with mucoproteose had the lowest incidence of AEs (4.1% for overall AEs, 3.7% for gastrointestinal AEs [GAEs]) and was used as the reference supplement in the regression model. Incidence rates of overall AEs for the other supplements were 7.3% for iron protein succinylate [GAEs: 7%; OR for AE compared to the reference supplement, 1.96], 23.5% for ferrous glycine sulfate [GAEs: 18.5%; OR: 5.90], 30.9% for ferrous gluconate [GAEs: 29.9%; OR: 11.06], 32.3% for ferrous sulfate without mucoproteose [GAEs: 30.2%; OR: 11.21], and 47.0% for ferrous fumarate [GAEs: 43.4%; OR: 19.87]. The differences in incidence of AEs between extended-release ferrous sulfate with mucoproteose and all other supplements except iron protein succinylate were statistically significant at p < 0.001. These findings are subject to some limitations as the designs and methodologies of the studies included show heterogeneity among them that has partially been counteracted by the large sample size provided by the substantial number of trials, which is considered a strength in tolerability studies. Extended-release ferrous sulfate with mucoproteose appears to be the best tolerated of the different oral iron supplements evaluated.